Damping‐off, root rot and wilting caused by Pythium myriotylum on Acacia crassicarpa in Sumatra, Indonesia. Issue 3 (25th April 2021) - Oliveira, Leonardo Sarno Soares; Jung, Thomas; Milenković, Ivan; Tarigan, Marthin; Horta Jung, Marília; Lumbangaol, Pantun David Mangatas; Sirait, Betti Andriany; Durán, Álvaro
Abstract: Acacia crassicarpa is a legume tree of rapid growth and high pulp yield and fibre quality, making this species the basis of large commercial plantations for pulpwood production in Southeast Asian countries. Since a disease has caused significant economic losses in a nursery in the province of Riau, Sumatra, Indonesia, this study aimed to identify the causal agent of the root rot, damping‐off and wilting symptoms of A .  crasicarpa seedlings. Isolations were made from infested soil by baiting with young leaves of native Quercus spp. from northern Sumatra. Classical identification using colony growth patterns and morphological characters, molecular identification based on ITS sequence analysis and direct PCR with specific primers, and pathogenicity tests were performed. All isolates formed typical Pythium structures and had fast growth, with optimum and maximum temperatures of 35 and 42°C, respectively. ITS sequence analysis of seven selected isolates showed 99.7–99.9% homology with Pythium myriotylum, the causal agent of nursery diseases on many crops. In addition, species‐specific primers Pmy5/ITS2 successfully yielded an expected amplicon of approximately 144 bp. A soil infestation trial under controlled conditions confirmed the pathogenicity of P .  myriotylum to A .  crassicarpa, with typical symptoms starting six days after inoculation. The pathogen was re‐isolated only from diseased inoculated plants fulfilling Koch's postulates. This is the first report of P .  myriotylum as a pathogen on A .  crassicarpa .